Expression-based intrinsic glioma subtypes are prognostic in low-grade gliomas of the EORTC22033-26033 clinical trial - Gao, Ya; Deimling, Andreas von (European journal of cancer, 2018)
Introduction - The European Organisation for Research and Treatment of Cancer (EORTC) 22033-26033 clinical trial (NCT00182819) investigated whether initial temozolomide (TMZ) chemotherapy confers survival advantage compared with radiotherapy (RT) in low-grade glioma (LGG) patients. In this study, we performed gene expression profiling on tissues from this trial to identify markers associated with progression-free survival (PFS) and treatment response. - Methods - Gene expression profiling, performed on 195 samples, was used to assign tumours to one of six intrinsic glioma subtypes (IGSs; molecularly similar tumours as previously defined using unsupervised expression analysis) and to determine the composition of immune infiltrate. DNA copy number changes were determined using OncoScan arrays. - Results - We confirm that IGSs are prognostic in the EORTC22033-26033 clinical trial. Specific genetic changes segregate in distinct IGSs: most samples assigned to IGS-9 have IDH-mutations and 1p19q codeletion, samples assigned to IGS-17 have IDH-mutations without 1p19q codeletion and samples assigned to other intrinsic subtypes often are IDH-wildtype. A trend towards benefit from RT was observed for samples assigned to IGS-9 (hazard ratio [HR] for TMZ is 1.90, P = 0.065) but not for samples assigned to IGS-17 (HR 0.87, P = 0.62). We did not identify genes significantly associated with PFS within intrinsic subtypes, although follow-up time is limited. We also show that LGGs and glioblastomas differ in their immune infiltrate, which suggests that LGGs are less amenable to checkpoint inhibitor-type immune therapies. Gene expression analysis also allows identification of relatively rare subtypes. Indeed, one patient with a pilocytic astrocytoma was identified. - Conclusion - IGSs are prognostic for PFS in EORTC22033-26033 clinical trial samples.